Electrospinning synthesis of transition metal alloy nanoparticles encapsulated in nitrogen-doped carbon layers as an advanced bifunctional oxygen electrode. Issue 15 (1st April 2020) - Cao, Feng; Yang, Xi; Shen, Chen; Li, Xin; Wang, Jianmin; Qin, Gaowu; Li, Song; Pang, Xueyong; Li, Guoqing
Abstract : A universal and scalable electrospinning method was developed to produce uniform multicomponent alloy nanoparticles encapsulated in N doped thin carbon layers as bifunctional catalysts for OER and ORR. Abstract : The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) play vital roles in various applications, including metal–air cells, fuel cells, and water decomposition devices. However, the slow dynamics of the ORR and OER are the key challenges limiting their efficiencies. Transition metals (TMs) and their alloys are promising catalysts for the ORR and OER. Herein, we develop a facile and robust method to prepare TM alloy nanoparticles encapsulated in nitrogen-doped carbon nanofibers as efficient bifunctional catalysts for both the OER and ORR. We find that this method can benefit the catalyst design in several ways. Firstly, the compositions of alloys (binary, ternary and quaternary alloys) can be well controlled. Secondly, alloy nanoparticles could be formed and uniformly distributed along the supporting carbon nanofibers which could avoid their aggregation. Additionally, the alloy nanoparticles are encapsulated by carbon layers and nitrogen atoms could be introduced easily into the carbon nanofibers and layers causing changes of their electronic structure, which can then improve the catalytic activity of metal alloy cores. Using this method, we prepared N-doped carbon encapsulating nickel, cobalt and iron alloys with a ratio of 1 : 1 : 1 as a bifunctional catalyst with remarkable activities for both the OER and ORR. d-Band theory calculations were used to explain the superior activities of the alloys. The assembled rechargeable Zn–air battery with the as-synthesized NiCoFe@N-CNFs shows a high specific capacity of ∼845 mA h gZn −1 with superior charge–discharge cycling durability. This work can provide an ideal platform to study the fundamental mechanism of catalytic processes involving complex metal alloy catalysts and to modify their catalytic activity at the atomic level.